Association between Metabolic Syndrome and Six Minutes Walk Distance on Elderly Pilgrims - Hendrawati Hendrawati (ACI (Acta Cardiologia Indonesiana), 2017)
Background: SISKOHATKES data on 2017 mentioned that the number of morbidity and .....